Exploring the Potential of Extracts from Sloanea medusula and S. calva: Formulating Two Skincare Gels with Antioxidant, Sun Protective Factor, and Anti-Candida albicans Activities - Patricia Quintero-Rincón; Ana C. Mesa-Arango; Oscar A. Flórez-Acosta; Carolina Zapata-Zapata; Elena E. Stashenko; Nayive Pino-Benítez (MDPI AG, 2023)
Sloanea is a plant genus, native to tropical regions, used in medicinal practices for its anti-inflammatory properties. This study aimed to determine the antioxidant activity, sun protective factor (SPF), and antifungal of extracts obtained from two species of Sloanea and to develop extract-based gels with antioxidants, photoprotective, and anti-Candida albicans effects. Ethanolic extracts from S. medusula and S. calva collected in Chocó, Colombia, were used for antioxidant activity and SPF determination using the DPPH assay and the Mansur equation, respectively. Extracts were characterized using HPLC-MS and used to prepare the gels. The viscosity of the extract-based gels was evaluated using an MCR92 rheometer. In addition, the anti-Candida activity of extracts against five yeasts and anti-C. albicans of gels were evaluated following the Clinical and Laboratory Standards Institute M27, 4th Edition. High DPPH radical scavenging activity (42.4% and 44.7%) and a high SPF value (32.5 and 35.4) were obtained for the extracts of S. medusula and S. calva, respectively. Similarly, extract-based gels showed significant DPPH radical scavenging activity of 54.5% and 53.0% and maximum SPF values of 60 and 57. Extract from S. medusula showed an important antifungal activity against C. albicans (minimal inhibitory concentration (MIC) of 2 µg/mL). In contrast, S. calva extract was active against C. krusei, C. albicans (MIC of 2 µg/mL) and C. tropicalis (MIC of 4 µg/mL). Sloanea medusula gel (0.15%) exhibited an important C. albicans growth inhibition (98%), while with S. calva gel (0.3%) growth inhibition was slightly lower (76%). Polyphenolic and triterpenoid compounds were tentatively identified for S. medusula and S. calva, respectively. Both extracts can be considered promising sources for developing photoprotective gels to treat skin infections caused by C. albicans.